On Stabilization Problem for Nonlinear Systems with Power Principal Part - Bebiya, M.O.; Korobov, V.I. (Журнал математической физики, анализа, геометрии, 2016)
In the present paper, the stabilization problem for the uncontrollable with respect to the first approximation nonlinear system with power principal part is solved. A class of stabilizing controls for the nonlinear approximation of this system is constructed by using the Lyapunov function method. It is proved that the same controls solve the stabilization problem for the original nonlinear system. An ellipsoidal approximation of the domain of attraction to the origin is given.